Building communities of health: the experience of European social clinics - Da Mosto, Delia; Vallerani, Sara; Kokkinidis, George; Checchi, Marco; Giaimo, Silvia; Adami, Elisa; Mammana, Leonardo (My University, 2023)
Social clinics are grassroots health initiatives characterized by the development of mutualist practices of healthcare provision and the articulation of their action at territorial and community level. The present paper explores the development and implementation of community participation practices across three social clinics in Europe: social clinic of solidarity KIA in Greece, Village2Santé in France, and Microclinica Fatih in Italy. Drawing on findings collected through qualitative methods, our paper reflects on three overlapping themes of community participation highlighting its collective and eminently political character. Inspired by the frameworks of health promotion, comprehensive Primary Health Care and community development, we analyze three levels of community participation in the social clinics: participatory medical practices, the co-creation of health services, and the connection with broader social movements. Our paper contributes to the literature on community development by stressing the urge to reimagine the principles and practices of community participation through the creation of alternative forms of organizing and of radical empowerment. At the same time, it can inspire practitioners in experimenting with community participation initiatives from a more critical perspective, resisting the worst elements of neoliberalism.